Pharmacists’ experiences on adverse drug reaction: 10 years later - Karuppannan, Mahmathi; Mohamad Rizal, Nur Azzrin Nisha; Wong, Kok-Thong; Mohd. Ali, Salmiah; Ting, Kang-Nee; Boardman, Helen (Frontiers in Pharmacology, 2022)
Adverse drug reaction (ADR) is one of the leading public health concerns associated with high mortality rate. Health care professionals particularly, pharmacists have a significant role in monitoring and preventing ADRs. This study was conducted on Malaysian Pharmaceutical Society (MPS) pharmacists who worked at the hospital, health clinic and community pharmacy to determine if pharmacists’ experiences on ADRs are still the same 10 years later. In 2010, a postal survey and in 2020 an online survey was conducted among these pharmacists. A total of 472 pharmacists and 208 participated in 2010 and 2020, respectively. About 82% and 90% of hospital/health clinic pharmacists (HCP) observed an ADR last 6 months in 2010 and 2020. While 60% and 100% community pharmacists in 2010 and 2020 observed an ADR. Perindopril was the top drug (HCPs p=0.657; CPs: p=0.98) and rash was the top ADR reported by the pharmacists in both years (HCPs p<0.001; CPs: p=0.679). The most common actions taken by HCP pharmacist in 2010 was to report the ADR (p=0.343) while in 2020 most HCPs explained to patient regarding the reaction (p=0.061), which was also the same in the CP group in 2020 (p=0.958). The top factor encouraging ADR reporting in both years and both pharmacist groups was high degree of severity of the reaction (HCPs p<0.001; CPs: p=0.769). While the top factors discouraging ADR reporting were a lack of information from the affected patients (HCPs p=0.2; CPs: p=0.656), reaction is widely known (HCPs p=0.001; CPs: p=0.144) and uncertainty of the causal relationship (HCPs p=0.169; CPs: p=0.609). Majority of the pharmacists agreed that severe reactions should be reported (HCPs p=0.158; CPs: p=0.501) and the main aims for reporting is to measure the incidence of ADRs (HCPs p=0.148; CPs: p=0.762). Despite being able to identify ADRs during the daily practice, many pharmacists especially community pharmacists are not reporting them. There is a misconception on the purpose of reporting ADRs. Interventional program and ADR reporting training would be a useful step in improving ADR reporting practice.